A PREDISPOSITION USING MORPHOLOGICALLY-CHANGED ENGLISH WORDS IN WRITING BY INDONESIAN EFL LEARNERS - Dwie Agustiani, Indah Windra; Gumartifa, Asti (Universitas Muhammadiyah Palembang, 2020)
This study aimed at investigating the reasons of Indonesia EFL learners in using morphologically- changed English words in writing and finding out the number of Morphologically Changed English Words tend to be used by Indonesian EFL learners at English study Program at FKIP UMP. The number of sample was 36 Indonesian EFL Learners at the third semester of English Study Program at FKIP UMP. This research was a descriptive study. The technique used for collecting the data was distributing questionnaire. The data was analyzed by using percentage analysis and explained descriptively. The results of this study showed that the majority of respondents had more than one reason for a predisposition using morphologically changed English Words in writing. What triggers the use of them was classified into 9 categories; Entertainment, Habit, Efficiency; Saving time and space, Simplification (Easeness), Esthetics, Narsistics, Self-Contentment, Uniqueness, and Trend/Environment. Self-contentment Reasoning is the most dominant reason that the respondents had. There were 1 sentence, 8 phrases, and 20 words tend to be changed morphologically by Indonesian EFL learners as language users. This research was hoped to give the contribution to sociolinguistic aspect that tries to investigate personal use of the language in society in written and it might be dealt with discourse analysis either. It also informed the language phonemenom happened among Indonesian EFL learners as language users and hoped to help other people understand the original language intention by EFL learners when writing such forms for avoiding misunderstanding.